On the Direction of Innovation - Hopenhayn, Hugo; Squintani, Francesco (Journal of Political Economy, 2021)
How are resources allocated across different R&D areas (i.e., problems to be solved)? As a result of dynamic congestion externalities, the competitive market allocates excessive resources into those of high return, being those with higher private (and social) payoffs. Good problems are tackled too soon, and as a result the distribution of open research problems in the socially optimal solution stochastically dominates that of the competitive equilibrium. A severe form of rent dissipation occurs in the latter, where the total value of R&D activity equals the value of allocating all resources to the least valuable problem solved. Resulting losses can be substantial.